2018
DOI: 10.1016/j.ijfoodmicro.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus in lettuce and water samples: A method-comparison study

Abstract: The hepatitis E virus (HEV), which is an increasing cause of acute viral hepatitis in Europe, is a zoonotic virus that is mainly transmitted through contaminated water, consumption of raw or undercooked meat from pigs or wild boar, blood transfusion, and organ transplantation. Although the role of HEV transmission through contaminated produce has not been confirmed, the presence of HEV has been reported in irrigation waters and in vegetables. The present study used a World Health Organization (WHO) internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Initially, two different RT-qPCRs were applied to assess HEV occurrence. Surprisingly, RT-qPCR1 showed a limited number of positives compared to RT-qPCR2 ( Figure 5) despite a previous study reported similar performance of these assays in influent water samples (Randazzo et al, 2018). Suspecting that a different HEV genotype was circulating, a third RT-qPCR assay was included in the study.…”
Section: Performance Of Rt-qpcr Assays Of Hev In Naturally Contaminatmentioning
confidence: 95%
“…Initially, two different RT-qPCRs were applied to assess HEV occurrence. Surprisingly, RT-qPCR1 showed a limited number of positives compared to RT-qPCR2 ( Figure 5) despite a previous study reported similar performance of these assays in influent water samples (Randazzo et al, 2018). Suspecting that a different HEV genotype was circulating, a third RT-qPCR assay was included in the study.…”
Section: Performance Of Rt-qpcr Assays Of Hev In Naturally Contaminatmentioning
confidence: 95%
“…HEV is transmitted mainly by the consumption of contaminated water or contaminated undercooked or raw food such as vegetables, meat (pork, mutton, rabbit, poultry) and dairy products [2,5,14,15]. It is important to note that contaminated water is not only a cause of direct transmission but is also related to indirect transmission due to its use in agriculture practices, namely in the irrigation of vegetables, where the virus may accumulate and be delivered as infectious particles [16][17][18][19][20]. Although less frequent, HEV can also be transmitted by transfusions with contaminated blood and by vertical (mother-to-child) transmission [14,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, three previously described HEV assays (Mansuy et al, 2004; Randazzo et al, 2018c) were coupled with two viability markers propidium monoazide (PMAxx) and platinum chloride (PtCl 4 ) and initially evaluated on purified viral RNA. The optimized viability RT-qPCR method was then applied to native, heat-, and high-pressure processing (HPP)-treated HEV to assess its performance in discriminating between potentially infectious and inactivated viral particles.…”
Section: Introductionmentioning
confidence: 99%